Explanation of the Compensation Law and the Isokinetic Point in the Electrical Conduction of Crosslinked Polyethylene. (7th February 2022) - Walker, Roger; Furman, Eugene; Woodward, William H. Hunter; Lanagan, Michael
Abstract : Thermally activated direct current (DC) electrical conductivity in low-density polyethylene (LDPE) is known to be subject to the compensation law. Accordingly, the preexponential factor follows a specific relation with activation energy, reducing overall changes in conductivity. This relationship is governed by the Meyer-Neldel temperature. However, there is no published evidence for a corresponding isokinetic point, a temperature where the conductivity of all LDPE samples is the same. Here, it is determined that the compensation law applies to both DC and alternating current (AC) conduction for LDPE and for crosslinked polyethylene (XLPE) without an observed isokinetic point. The potential origins of compensation in polyethylene are discussed as well as reasons for similarity between LDPE and XLPE. It is observed that prolonged water exposure removed the compensation behavior. Meanwhile, preheating samples in the oven prior to measurements modifies the compensation behavior and reduced the spread around the isokinetic point. It is thus deduced that an isokinetic point can be observed in polyethylene but is obscured by contributions from water and other impurities.